Procedures for Developing Bilingual Children Storybook Based on Caring Character - M Tolkhah Adityas (Universitas Ahmad Dahlan, 2019)
This study reveals the procedures for developing bilingual children storybook based on caring character for elementary school students. This is a research and development with descriptive qualitative as data analysis technique. The process of developing bilingual children storybook consists of five stages of development procedures, namely 1) preliminary studies including analysis of students’ needs, characteristics, potential, and problems, 2) planning including literature review and formulating learning objectives, 3) initial product development including determining themes, plot, illustrations, story elements, and expert validation, 4) preliminary field testing, and 5) product revision. The bilingual children storybook based on caring values has been validated by media, material, and pedagogical experts and declared appropriate for use. According to media experts and material experts, the product is categorized